The Influence of Greco-Roman Literature on the Poetry of Ahmad Shawqi - Al-Rifai, Nada Yousuf (Advances in Social Sciences Research Journal, 2018)
The paper consists of an introduction and three main parts. Part I is a reading of Shawqi’s poem "Aristotle." Part II deals with Shawqi’s epic poetry. Part III looks at Shawqi’s poetic theater. Ahmad Shawqi (1868–1932) was one of the finest Arabic-language poets and dramatists to pioneer the modern Egyptian literary movement; Shawqi was most notable for introducing poetic epics and drama to the Arabic literary tradition. Shawqi, deemed the “Prince of Poets” and one of the greatest Arabic poet laureates, was raised in a privileged setting with Turkish, Kurdish, Circassian, Greek, and Arab roots. As Shawqi was very relevant to the Khedive Palace, the Khedive sent him, in the late nineteenth century, to France to continue his studies in law and learn about French literature at the Universities of Montpellier and Paris. While in France, he was heavily influenced by the works of French playwrights, most notably Molière and Racine. The evident phenomenon in Shawqi’s epic and theatrical poetry is influenced by the French classical school, which derived its subjects from the tragedies of Greek and Roman history. In this pattern, Shawqi derived the topics of his tragedies from Egyptian and Arab history.